Тайна старого кладбища: повесть / А.Д. Иванов, А.В. Устинова - Иванов Антон Давидович (Братство кленового листа, 2003)
Экземпляры: Д.О. (20200703) / Инвентарный номер: 38955 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: И20 / ББК: 84(2=411.2)6-44